Chest tube management in patients undergoing lobectomy - Shintani, Yasushi; Funaki, Soichiro; Ose, Naoko; Kanou, Takashi; Kanzaki, Ryu; Minami, Masato; Okumura, Meinoshin (Journal of Thoracic Disease; Vol 10, No 12 (December 30, 2018): Journal of Thoracic Disease, 2018)
Full expansion of remaining lung tissue is the most important issue following a pulmonary lobectomy, for which chest tubes are used for proper drainage of both air and fluid, with the outflow considered to reflect the condition of the thoracic cavity after surgery (1,2).